Macroeconomic Effects of Chinas Fiscal Stimulus - Pietro Cova; Massimiliano Pisani; Alessandro Rebucci (Inter-American Development Bank (IDB), 2010)
This paper analyzes the macroeconomic impact of Chinas 2009-2010 fiscal stimulus package by simulating a dynamic general equilibrium multi-country model of the world economy, showing that the effects on Chinas economic activity are sizeable: absent fiscal stimulus Chinas GDP would be 2.6 and 0.6 percentage points lower in 2009 and 2010, respectively. The effects are stronger under a US dollar peg because of the imported loose monetary policy stance from the United States. Higher Chinese aggregate demand stimulates higher (gross and net) imports from other regions, in particular from Japan and the rest of the world, and, only to a lesser extent, from the United States and the euro area. However, the overall GDP impact of the Chinese stimulus on the rest of the world is limited. These results warn that a fiscal policydriven increase in Chinas domestic aggregate demand associated with a more flexible exchange rate regime have only a limited potential to contribute to an orderly resolution of global trade and financial imbalances.
Keywords: E62; F41; F42; H30; H63; 330; Fiscal stimulus; Financial crisis; Antizyklische Finanzpolitik; Finanzkrise; Makroökonomischer Einfluss; China